EXPERT SYSTEM DIAGNOSIS OF OVARIUM CELL DISEASE USING CERTAINTY FACTOR METHOD WEB-BASED - Ni'matu Zahroh; Yulian Findawati (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2018)
Ovarian cyst disease is a disease that is often experienced by a woman, the disease is very complicated, smooth and unique, because this disease mirim with pregnancy and could be all women have the risk of this disease.The expert system of ovarian cyst disease diagnosis is a web application that allows users to diagnose ovarian cyst disease they are experiencing. The purpose of making this application is to facilitate the user in diagnosing the type of ovarian cyst disease based on the symptoms that are being felt.In the use of expert system application of this ovarian cyst disease diagnosis, the user must register first to get a username and password that will be used to log on expert system and diagnose ovarian cyst disease. The method used is certainty factor that is by accommodating the uncertainty of an expert's thinking, or expressed the belief in an event that is fact or hypothesis.